The Italian Code of Medical Deontology. Historical, ethical and legal issues - Patuzzo, Sara; De Stefano, Francesco; Ciliberti, Rosagemma (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: Medical deontology is increasingly important, owing to the interests and rights which the medical profession involves. This paper focuses on the relationships of the Italian Code of Medical Deontology (CMD) with both the ethical and legal dimensions, in order to clarify the role of medical ethics within the medical profession, society and the overall system of the sources of law. Methods: The authors analyze the CMD from an ethical perspective and through the new doctrinal guidelines and current trends in the Italian law courts. Results: From an ethical point of view, moral philosophical analysis scarcely seems to address professional medical ethics. Nonetheless, the CMD needs to undergo careful ethical analysis. From a legal perspective, the Italian CMD contains provisions which do not have an official legal nature. However, they are directly binding for medical practitioners, and therefore could be understood as a supplement to the general rules of the legal system. Conclusions: At an ethical level, rigorous debate on the CMD is indispensable, in order to update its specific principles and to make it a real moral normative document. At a legislative level, there is a possible contradiction between a legal system that does not take into account the CMD, but which then attributes significant importance to the violation of its rules.